Pertunjukan Panggung Musikal : Sebuah Bentuk Imaji Baru Medium Berkarya Post-Sinema Sineas Indonesia - Nugroho, Widhi (Seni Media Rekam ISI Surakarta, 2011)
Today the musical theatre is a new performance art that was created by famous Indonesian filmmakers. Convensional elements in the film production combine with visual display on the musical performances creatively and elegantly. The drastically change in film became a medium of show, provide a change not merely in terms of visual-physical, but more change in the context, especially meaning, the message will be delivered by the musical art. It is Â a new phenomenon in the Indonesian entertainment.Keywords: performing arts, musical theatre, post-cinema.